PENGARUH PENGGUNAAN MEDIA ANIMASI TERHADAP HASIL BELAJAR PKN SISWA KELAS KELAS III SD - Nurul Yuda; Siti Halidjah; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research intended to analyze the effect of the use of animation media on student learning outcomes in learning Citizenship Education in class III of South Pontianak 36 Primary School. The method used is an experiment in the form of a Quasi Experimental Design design and a non equivalent control group design. The population is all students from two classes totaling 44 people, the sample of this study is class IIIA students, amounting to 21 people as the experimental class and class IIIB students as the control class of 23 people. The data collection technique used is the measurement technique and the data collection tool is a written test in the form of multiple choice. Based on the analysis of the data obtained the average results of the experimental class post-test class 75.88 and the average post-test control 70.54. Hypothesis test results using t-test (Polled Variance) obtained tcount = 2.411 while for dk (21+23-2 = 42) with a significant level α = 5% obtained ttable = 1.681, which means tcount> ttable, then Ha is accepted, this prove that there is an influence of the application of animation media in Civics Education Learning. Based on the results of the calculation of the effect size (ES) obtained ES = 0.50 including medium criteria. Keywords: Influence, Animation Media, Civic Education, Learning Outcomes